Multistep microsatellite mutation at D18S51 locus in a parentage testing case. (December 2017) - Yang, Yaran; Ren, He; Yang, Meng; Li, Chen; Liu, Yacheng; Yan, Jiangwei
Abstract: Mutations of short tandem repeats (STRs) loci might cause allelic mismatchs between the child and the parents, which entangled the forensic inference in paternity testing. Most of the reported microsatellite mutations are confined to single-step mutations, and multistep mutations were rarely reported and only account for a very limited number of STR mutation events in previously studied cases. Here we reported a paternity case with a mismatch in locus D18S51. The genotypes of the alleged father, the mother and the child in D18S51 locus were 14/23, 15/16, and 15/20, respectively. Examination of 38 autosomal STR loci revealed no mismatches, and the paternity index is above 1.58E + 15. These results suggested that the alleged father is the biological father of the child that a rare three-steps mutation had occurred in the paternal allele of D18S51.